2009
DOI: 10.1111/j.1365-2427.2009.02203.x
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater biodiversity patterns in the Lessinian Massif of northern Italy

Abstract: SUMMARY1. The distribution patterns of stygobiotic invertebrates were examined with a stratified sampling design at 197 sites selected among four hydrogeographic basins in the Lessinian Massif (northern Italy). The sites were approximately evenly distributed among four hydrogeological zones: unsaturated and saturated zone of karstic aquifers, and hyporheic and saturated zone of porous aquifers. 2. Outlying Mean Index (OMI) analysis which assesses deviation of habitat conditions from reference conditions, was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(89 citation statements)
references
References 28 publications
(50 reference statements)
6
83
0
Order By: Relevance
“…In contrast, the benthic species rarely occurred in the temporary springs but the species abundantly present in the drift of the perennial spring were often collected also in the drift from the temporary springs, what is indicative of interconnectivity of the two zones. Galassi et al (2009b) observed a higher regional distributional rarity of the species from the vadose zone compared to that in the phreatic zone, which was not the case in this study where only one site was investigated. Here the species richness was the highest in the drift from the perennial spring.…”
Section: Microcrustaceans In the Alpine Karstic Aquifermentioning
confidence: 54%
See 3 more Smart Citations
“…In contrast, the benthic species rarely occurred in the temporary springs but the species abundantly present in the drift of the perennial spring were often collected also in the drift from the temporary springs, what is indicative of interconnectivity of the two zones. Galassi et al (2009b) observed a higher regional distributional rarity of the species from the vadose zone compared to that in the phreatic zone, which was not the case in this study where only one site was investigated. Here the species richness was the highest in the drift from the perennial spring.…”
Section: Microcrustaceans In the Alpine Karstic Aquifermentioning
confidence: 54%
“…At a regional scale, historical variables (glaciations and the age of geological formations), altitude and geology (pore size) primarily determined the hypogean community composition and species richness (Dole-Olivier et al, 2009a). A comparison of the vadose and phreatic zones revealed higher regional species richness in the former (Dole-Olivier et al, 2009b;Galassi et al, 2009b;Galassi et al, 2013), most probably due to higher habitat heterogeneity and habitat fragmentation.…”
Section: Study Sitementioning
confidence: 99%
See 2 more Smart Citations
“…Diurnal temperature fluctuations are typically found at depths of less than 1 m, but seasonal fluctuations may be detectable at depths up to 15 m [10]. The annual amplitude of temperature is typically less than 2 • C in porous aquifers that are deeper than 5 m below the soil surface [11][12][13][14][15]. Yet, shallow porous aquifers are not immune to global warming, because the annual mean temperature of groundwater closely tracks the ambient air temperature [11].…”
Section: Introductionmentioning
confidence: 99%